Tratado sobre o sistema de telhado verde extensivo para coberturas planas em edificações de pequeno e médio porte - Dilly, Diogo Pedro Appel (Universidade do Vale do Rio dos Sinos, 2017)
Humanity has been depleting natural resources at an unprecedented speed being the construction industry one of the biggest responsible for it. Sustainable practices exist to direct and influence projects, materials, systems and technologies so that they become ecologically correct, socially just, and economically viable. The green roof appears as a project solution of extreme expression next to the concepts of sustainable development. Considering the lack of technical material, the present work could be stated as a way to bring the characteristics of this system into a document in the form of a treaty, that lecture one or more subjects in a didactic way about an specific science. This study deals with the Extensive Green Roof system in flat roof covers for small and medium size buildings. The research was elaborated in three parts: historical contextualization - understanding the green roof as being an ancient element in architecture with new uses – green roof types and components: listing the Extensive Green Roof as the object of the research – and the characteristics of the green roof system: explaining the system benefits along with sustainable practices. The choice of the green roof type between "traditional" and "laminar" may have a greater influence on the design of the structures, as well as the choice of substrate and vegetation type. The vegetation also depends on the intended use for the green roof, with grass being the most common type to gain floor area. The green roof can be considered a sustainable system because it can collaborate in the management of rainwater by absorbing part of the water in the system itself, due to the vegetation, substrate and draining layer. The vegetation of the system can also help mitigate the effects of heat islands, reducing temperatures around them and improving air circulation in urbanized areas. The temperature can also be more easily controlled by the green roof system, which works as an excellent thermal insulation, not letting the heat enter the building during the summer and holding the heat inside the building in the winter. This makes energy expenditures considerably smaller. Some countries, including Brazil, consider the use of the green roof system as being of extreme importance.
Keywords: Humanidade; Recursos; Ecologicamente; Telhado; Humanity; Resources; Ecologically; Roof; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo